Citric Acid: A Multifunctional Pharmaceutical Excipient - Maria Lambros; Thac (Henry); Qinqin Fei; Mike Nicolaou (MDPI AG, 2022)
Citric acid, a tricarboxylic acid, has found wide application in the chemical and pharmaceutical industry due to its biocompatibility, versatility, and green, environmentally friendly chemistry. This review emphasizes the pharmaceutical uses of citric acid as a strategic ingredient in drug formulation while focusing on the impact of its physicochemical properties. The functionality of citric acid is due to its three carboxylic groups and one hydroxyl group. These allow it to be used in many ways, including its ability to be used as a crosslinker to form biodegradable polymers and as a co-former in co-amorphous and co-crystal applications. This paper also analyzes the effect of citric acid in physiological processes and how this effect can be used to enhance the attributes of pharmaceutical preparations, as well as providing a critical discussion on the issues that may arise out of the presence of citric acid in formulations.